2004
DOI: 10.1002/j.1939-4640.2004.tb02849.x
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Testicular Arteries During Subinguinal Microsurgical Varicocelectomy: Clinical Considerations

Abstract: Microsurgical varicocelectomy with intentional preservation of the testicular artery(ies) is regarded as the gold standard approach to varicocele repair. We sought to determine whether the number of testicular arteries preserved at the time of micro-surgical varicocelectomy predicts improvement in postoperative semen parameters. We analyzed the records of 334 infertile men who underwent varicocelectomy performed by a single surgeon using a subinguinal microsurgical technique between July 1996 and January 2003.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…46,48 In a number of studies, it has been shown that microsurgical varicocelectomy (inguinal or subinguinal) is superior to non-microsurgical procedures with respect to the development of postoperative complications such as hydrocele or recurrence. 41,46,47 Hydrocele formation is believed to be due to ligation of lymphatic channels and recurrence generally results from incomplete ligation of collateral venous channels. 53,54 Magnification of the spermatic cord with the use of the operating microscope reduces the potential for development of such complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…46,48 In a number of studies, it has been shown that microsurgical varicocelectomy (inguinal or subinguinal) is superior to non-microsurgical procedures with respect to the development of postoperative complications such as hydrocele or recurrence. 41,46,47 Hydrocele formation is believed to be due to ligation of lymphatic channels and recurrence generally results from incomplete ligation of collateral venous channels. 53,54 Magnification of the spermatic cord with the use of the operating microscope reduces the potential for development of such complications.…”
Section: Discussionmentioning
confidence: 99%
“…53,54 Magnification of the spermatic cord with the use of the operating microscope reduces the potential for development of such complications. 41,46,47 However, microsurgical varicocelectomy, particularly the subinguinal approach, remains a technically challenging procedure that requires microsurgical expertise. This article has been peer reviewed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a hydrocele occurred in the open inguinal group, whereas no hydroceles or testicular atrophy occurred in the LESS group after spermatic artery scarifying. In addition, Grober et al 20 suggested that the number of arteries identified and preserved with meticulous spermatic cord dissection during subinguinal varicocelectomy does not correlate with clinical outcomes. Therefore, the effort of lymphatics and testicular artery sparing during LESS varicocele ligation made the difference of clinical outcomes insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…2). Testicular artery(ies) was confirmed by the visualization of clear pulsatile movement [10], with the magnification and sometimes the use of papaverine, it is easy to identify the testicular artery Figure 1b showed the same field under operating microscope (89) World J Urol at inguinal level. In the end, all the internal spermatic veins were ligated; the lymphatics, arteries, and vas deferensassociated vessels were preserved.…”
Section: Techniquementioning
confidence: 92%